THE ROLE OF THE STEREOTYPES IN THE SOCIAL RELATIONS - Sattorovich, Jumaev Ulugbek (International Journal of Psychosocial Rehabilitation, 2020)
This paper analyses the role of the stereotypes in the social relations. On this case, social relations of the society and the influence of the stereotypes were discussed as the whole. Finally, research has concluded with the major points of the research with both outcomes and shortcomings.